Espécies ácidas gasosas e íons majoritários no material particulado atmosférico de uma região agriícola do Mato Grosso - Santos, Oalas Aparecido Morais dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Anthropogenic processes, such as agriculture, livestock, biomass burning, industrial activities, among others, have contributed to rapid changes in atmospheric composition, particularly component traces, with consequences for the climate, biodiversity and biogeochemical cycles essential nutrients such as nitrogen, sulfur and carbon. The State of Mato Grosso stands out on the national scene by farming, being responsible for 25% of Brazilian agricultural production, especially soybeans, cotton and corn. The Mato Grosso livestock is also featured in the Brazilian market, mainly with livestock, with the state vying for the top positions in the ranking of the sector. Apart from agricultural activities, the state has a significant number of fire outbreaks and wildfires, especially during dry months, which occurs from July to October. The sampling sites were inserted in the municipalities of Campo Verde (CV) and Jaciara (JC). Sampling was conducted in the rainy seasons 2012, 2012 and Dry Cleaning 2013 species of interest present in particulate matter (MP) and gaseous phase were collected using active sampling on filters with a diameter of 47 mm in the samplers filter pack type arranged in series in the following order: polycarbonate filter with a porosity of 12 ?m Teflon filter of 1 ?m and cellulose filter impregnated with Na2CO3 to collect acid gases. The extraction of ionic species and MP in the gas phase was carried out using 0.5 mL of isopropanol and 4.5 mL of deionized water. By ion chromatography the concentrations of ionic species Na+, K+, NH4+, Mg2+, Ca2+, Cl-, NO3-, SO42-, C2O42- e PO43- em MP>12 ?m e MP>1 ?m.. The cations most abundant in fractions of MP from both sites were Ca2+, NH4+ e K+ and SO42-, NO3- e PO43- anions. The highest concentrations for MP> 1 ?m CV were found in NH4+ (2149 ng m-3), K+ (1811 ng m-3), SO42- (2265 ng m-3) e NO3- (460 ng m-3). The highest concentrations in...
Keywords: Química ambiental; Agricultura; Pecuaria; Biomassa; Biodiversidade; Soja; Algodão; Milho; Environmental chemistry